Concentration Effect of Ferrofluids in Ferrogels on Their Magnetic and Magneto-elasticity Behaviors. (2019) - Sunaryono; Hidayat, Muchlis Fajar; Yogihati, Chusnana Insjaf; Taufiq, Ahmad; Mufti, Nandang; Rahmawati, Retno
Abstract: Polyvinyl Alcohol-based Ferrogels embedded with ferrofluids were successfully fabricated through the freezing-thawing process. Fe3 O4 nanoparticles were synthesized from iron sand using co-precipitation method with particles average size of 12 nm obtained from XRD data analysis and coincided with the morphology analysis using TEM. Furthermore, magnetic properties of ferrogels measured by VSM showed that the saturation magnetization of the ferrogels with TMAH composition of 1.4 mL was the highest. It indicated that the ferrogel with TMAH composition of 1.4 mL was the maximum composition to stabilize the ferrofluid. Additionally, a high the ferrofluid percentage in the ferrogels, the threshold magnetic field reduced.